A Molecular Basis for the Inhibition of Transient Receptor Potential Vanilloid Type 1 by Gomisin A. (26th October 2017) - Lee, Sung Bae; Noh, Shinhwa; Yeom, Hye Duck; Jo, Heejin; Eom, Sanung; Kim, Yoon Suh; Nam, Sangsoo; Bae, Hyunsu; Lee, Jun-Ho
Abstract : Transient receptor potential (TRP) channel has critical actions as conditional sensors in primary afferent neurons. We studied the regulatory action of gomisin A on TRPV1 channel current in this report. Schisandra chinensis contains bioactive compounds such as the gomisin derivatives and their related compounds. Coapplication with gomisin A inhibited the capsaicin-mediated inward peak current. This inhibitory effect of gomisin A on capsaicin-induced inward current showed concentration-dependence and was reversible. The half maximal inhibitory concentration of gomisin A was 62.7 ± 8.4 µ M. In addition, this inhibition occurred in a noncompetition regulation mode and voltage insensitive manner. Furthermore, molecular docking studies of gomisin A on TRPV1 showed that it interacted predominantly with residues at cavities in the segments 1 and 2 of each subunit. Four potential binding sites for this ligand in the extracellular region at sensor domain of TRPV1 channel were identified. Point mutagenesis studies were undertaken, and gomisin A potency decreased for both the Y453A and N467A mutants. The double mutation of Y453 and N467 significantly attenuated inhibitory effects by gomisin A. In summary, this study revealed the molecular basis for the interaction between TRPV1 and gomisin A and provides a novel potent interaction ligand.